Keamanan Nasional dalam Konteks Isu-isu Global Kontemporer: Sebuah Tinjauan Hubungan Internasional - Amaritasari, Indah Pangestu (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2017)
This article discusses global issues and its relation with national security. Global contemporary issues—drugs, migration, living environment, population, global economy challenges, liberal democracy crisis, fusion and division, small arms production—are issues that emerged as new security threats that transformed since the end of the Cold War. Security threats are no longer in form of “military attacks” that one country does to another, but are acts of crime that are performed by non-state actors and are aimed at state actors, individuals or citizens that ultimately threaten human security. Human security is a new term in response of threats from global contemporary issues. This article concludes that national security in the context of global contemporary issues in an international relations perspective is a complex issue. This is explained in the transnational theory in international relations. United Nations have reassessed the concept of national security which then noted about human security.